2004
DOI: 10.1021/ma030455j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Particle Size and Particle Size Ratio on the Morphology and Viscoelastic Properties of Bimodal Hard/Soft Latex Blends

Abstract: The morphology and viscoelastic properties of films prepared from bimodal latex blends containing equal weight fractions of soft and hard latex particles were investigated as a function of the particle sizes and the particle size ratio (soft particle diameter/hard particle diameter). Minimum film formation temperature (MFT) measurements were associated with transmission electron microscopy (TEM) to emphasize the particle size ratio dependence of the film formation properties. A significant increase of the MFT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 60 publications
5
60
0
Order By: Relevance
“…In addition, Christensen and Lo's three-phase model [126], Mori-Tanaka method, self-consistent method, Halpin and Kardos' model [127] of micromechanics can also be extended to account for the interface effect by including an interphase region between the matrix and particles [128,129]. For instance, Colombini et al [130,131] used the self-consistent scheme based on a ''particle-interphase-matrix" three-phase unit cell model to study the influence of the particle size and shape on the mechanical properties of bimodal hard/soft latex blends. They found that the smaller the size of the hard particles, the better the mechanical enhancement of the mechanical film properties.…”
Section: Theories For Elastic Modulusmentioning
confidence: 99%
“…In addition, Christensen and Lo's three-phase model [126], Mori-Tanaka method, self-consistent method, Halpin and Kardos' model [127] of micromechanics can also be extended to account for the interface effect by including an interphase region between the matrix and particles [128,129]. For instance, Colombini et al [130,131] used the self-consistent scheme based on a ''particle-interphase-matrix" three-phase unit cell model to study the influence of the particle size and shape on the mechanical properties of bimodal hard/soft latex blends. They found that the smaller the size of the hard particles, the better the mechanical enhancement of the mechanical film properties.…”
Section: Theories For Elastic Modulusmentioning
confidence: 99%
“…This is consistent with previously reported results that the spherical shape of hard particles is retained when the annealing temperate is below the T g of the hard component. 3,23 No voids were observed on the surface of the films made from pure Latex A and Latex B dispersions. 51 Although the addition of nonfilm-forming (hard) particles to a film-forming latex is known to generate voids in the film.…”
Section: Heat-induced Topography Changes In the Latex Blend Filmsmentioning
confidence: 94%
“…When the size ratio is slightly over 1.0 (as in the present case), the soft components are known to act as a continuous phase whereas hard particles disperse unevenly and voids are formed. 3 In the flat phase, the Latex A particles have lost their topographical identity, including their curvature at the latex-air interface [ Fig. 5(B)].…”
Section: Heat-induced Topography Changes In the Latex Blend Filmsmentioning
confidence: 99%
“…DMTA is a powerful technique for the study of blends of polymers. 15,16 Although only a relatively small amount of hard polymer was incorporated, this hard polymer seemed to dominate completely the mechanical properties of the film. In this specific case when only 16.5 wt% of hard polymer was added, the loss tangent tan d (E¢¢/E¢) showed the dominant presence of hard polymer.…”
Section: Interaction Between the Different Polymersmentioning
confidence: 99%